H-man : customized handle for a 2D planar robot - Foo, Ming Jeat (2016)
In the past few years many robotic devices have been developed to assist the physiotherapy on motor relearning and rehabilitation for stroke patients. H-Man, a planar manipulandum was introduced as a low cost and portable platform for upper arm rehabilitation. In order to improve its effectiveness and suitability, the functionality of the device is enhanced to allow vertical movement, as well as grip strength sensing. The end effector, i.e. handle, of the robot was modified in this project. Two strain gauge load cells were attached to the handle for force measurement. The handle provides a cylindrical gripping surface, a part of which slides along a horizontal railway before coming into contact with the load cells to transmit force. A reflective infrared sensor was installed to determine the vertical displacement of the handle from the H-Man base structure. The model shows accurate sensing for the vertical displacement and low grip force. The paper presents the design and development process, and the evaluation of the prototypes built.